Method for producing fluoroolefin

By using an α-alumina catalyst with a fine pore size of more than 5 nm and controlling the process conditions, the problems of low conversion and long-term decline in the existing fluoroolefin manufacturing methods are solved, and the high conversion and catalyst durability are improved.

CN119894858APending Publication Date: 2025-04-25AGC INC
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202380065975.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-11-14
Filing Date
2023-06-23
Publication Date
2025-04-25

AI Technical Summary

Technical Problem

In the conventional fluoroolefin production method, when γ-alumina or α-alumina with an average pore size of 3.20 nm is used as the catalyst, the conversion rate is low and the conversion rate decreases significantly during long-term production.

Method used

A catalyst containing α-alumina is used, with an average pore size of more than 5 nm and fluorinated hydrocarbons contact the catalyst at a temperature of 300 to 800°C. The contact time is controlled to be 0.5 to 100.0 seconds, and the pore volume of the catalyst is 0.002 to 1.20 cm3/g.

Benefits of technology

The conversion rate of fluoroolefins is improved, and the conversion rate decrease during long-term manufacturing is suppressed, and the durability of the catalyst is also improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005310314030000221
    Figure BDA0005310314030000221
  • Figure BDA0005310314030000222
    Figure BDA0005310314030000222
Patent Text Reader

Abstract

A method for producing a fluoroolefin, which comprises a step for producing a fluoroolefin represented by formula (2) by bringing a fluorohydrocarbon represented by formula (1) into contact with a catalyst that contains alpha-alumina and has an average pore diameter of 5 nm or more. (1) CX1X2F-CX3X4H... (1) CX1X2 = CX3X4... (2). In formula (1) and formula (2), X1, X2, X3, and X4 each independently represent a hydrogen atom or a fluorine atom, and at least one of X1, X2, X3, and X4 is a fluorine atom.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a method for preparing fluoroolefins. Background Art

[0002] In recent years, fluoroolefins have attracted attention as compounds with low global warming potential.

[0003] For example, Patent Document 1 describes a method for producing fluoroolefins, which includes a dehydrofluorination step of dehydrofluorinating a fluorocarbon by contacting the fluorocarbon with a metal catalyst, the dehydrofluorination step being carried out in a gas phase in the presence of water, the concentration of water being 500 ppm relative to the fluorocarbon, and using γ-alumina as a catalyst. In addition, Non-Patent Document 1 describes a method for obtaining trifluoroethylene by using α-alumina having an average pore diameter of 3.20 nm in the dehydrofluorination reaction of 1,1,1,2-tetrafluoroethane. Prior art literature Patent Literature

[0004] Patent Document 1: Japanese Patent Application Publication No. 2019-196347 Non-patent literature

[0005] Non-patent document 1: Catalysis Letters 2015, Vol. 145, p654-661 Summary of the invention Technical problem to be solved by the invention

[0006] However, when γ-alumina is used as a catalyst as described in Patent Document 1, the conversion rate tends to decrease during long-term production. In addition, when α-alumina having an average pore size of 3.20 nm is used as a catalyst as described in Non-Patent Document 1, the conversion rate is 1.2%, which is very low.

[0007] An object of one embodiment of the present invention is to provide a method for producing fluoroolefins which has a higher conversion rate than conventional methods and suppresses a decrease in the conversion rate during long-term production. Solutions to technical problems

[0008] The present invention includes the following aspects. <1> A method for producing a fluoroolefin, comprising the step of contacting a fluorocarbon represented by the following formula (1) with a catalyst to produce a fluoroolefin represented by the following formula (2): The catalyst contains α-alumina, The average pore diameter of the catalyst is above 5 nm. CX 1 X 2 F-CX 3 X4 H……(1) CX 1 X 2 =CX 3 X 4 ……(2) In formula (1) and formula (2), X 1 , X 2 , X 3 and X 4 Each independently represents a hydrogen atom or a fluorine atom, X 1 , X 2 , X 3 and X 4 At least one of them is a fluorine atom. <2> The method for producing a fluoroolefin according to <1>, wherein the catalyst contains 65 mass % or more of α-alumina. <3> The method for producing a fluoroolefin according to <1> or <2>, wherein the fluorohydrocarbon and the catalyst are brought into contact at a temperature of 300 to 800°C. <4> The method for producing a fluoroolefin according to any one of <1> to <3>, wherein the contact time between the fluorohydrocarbon and the catalyst is 0.5 to 100.0 seconds. <5> The method for producing a fluoroolefin according to any one of <1> to <4>, wherein the contact time between the fluorohydrocarbon and the catalyst is 1 to 200 g·sec / mL. <6> The method for producing a fluoroolefin according to any one of <1> to <5>, wherein the catalyst has an average pore diameter of 5 to 200 nm. <7> The method for producing a fluoroolefin according to any one of <1> to <6>, wherein the pore volume of the catalyst is 0.002 to 1.20 cm 3 / g. <8> The method for producing a fluoroolefin according to any one of <1> to <7>, wherein the catalyst is a molded body. <9> The method for producing a fluoroolefin according to any one of <1> to <8>, wherein the fluorocarbon is at least one selected from 1,1,1-trifluoroethane, 1,1,2-trifluoroethane, 1,1,2,2-tetrafluoroethane and 1,1,1,2-tetrafluoroethane. <10> The method for producing a fluoroolefin according to any one of <1> to <9>, wherein the fluoroolefin is at least one selected from the group consisting of 1,2-difluoroethylene, 1,1-difluoroethylene and trifluoroethylene. <11> The method for producing a fluoroolefin according to any one of <1> to <10>, wherein the fluorohydrocarbon is 1,1,1,2-tetrafluoroethane and the fluoroolefin is trifluoroethylene. <12> The method for producing a fluoroolefin according to any one of <1> to <11>, wherein the fluorocarbon and the catalyst are brought into contact in the presence of an inert gas, The inert gas is at least one selected from nitrogen, helium, argon, octafluorocyclobutane and carbon dioxide. <13> The method for producing a fluoroolefin according to any one of <1> to <12>, further comprising a step of drying the catalyst before bringing the fluorocarbon into contact with the catalyst. <14> The method for producing a fluoroolefin according to any one of <1> to <13>, wherein the fluorocarbon and the catalyst are brought into contact in a gas phase in the presence of water, The concentration of the water is less than 500 ppm based on the total amount of the raw material gas containing the fluorinated hydrocarbon. <15> The method for producing a fluoroolefin according to any one of <1> to <14>, wherein a conversion rate after 10 hours from the contact of the fluorocarbon with the catalyst is 30% or less. Effects of the Invention

[0009] According to the present invention, there is provided a method for producing fluoroolefins in which the conversion rate is higher than that in the related art and a decrease in the conversion rate is suppressed during long-term production. DETAILED DESCRIPTION

[0010] In the present disclosure, a numerical range expressed by “to” includes a range in which the numerical values ​​described before and after “to” are the minimum value and the maximum value, respectively. In the numerical ranges recorded in the present disclosure, the upper limit or lower limit recorded in one numerical range may also be replaced by the upper limit or lower limit of the numerical range recorded in other classifications. In addition, in the numerical ranges recorded in the present disclosure, the upper limit or lower limit of the numerical range may also be replaced by the value shown in the embodiments. In the present disclosure, a combination of two or more preferred embodiments is a more preferred embodiment. In the present disclosure, when there are plural substances corresponding to each component, the amount of each component refers to the total amount of the plural substances unless otherwise specified.

[0011] [Method for producing fluoroolefin] The method for producing fluoroolefins of the present invention comprises the step of contacting a fluorocarbon represented by the following formula (1) with a catalyst to produce a fluoroolefin represented by the following formula (2), wherein the catalyst contains α-alumina and has an average pore size of 5 nm or more. CX 1 X 2 F-CX 3 X 4 H……(1) CX 1 X 2 =CX 3 X 4 ……(2) In formula (1) and formula (2), X 1 , X 2 , X 3 and X 4 Each independently represents a hydrogen atom or a fluorine atom, X 1 , X 2 , X 3 and X 4 At least one of them is a fluorine atom.

[0012] According to the method for producing fluoroolefins of the present invention, the conversion rate is higher than that of conventional methods, and the decrease in the conversion rate is suppressed during long-term production. The reason for this is not yet clear, but it is presumed as follows.

[0013] Hydrogen fluoride is generated in the reaction of obtaining a fluoroolefin represented by formula (2) from a fluorocarbon represented by formula (1). The generated hydrogen fluoride reacts with the fluoroolefin represented by formula (2) to undergo a reaction to convert it back into a fluorocarbon represented by formula (1), so the conversion rate of the fluorocarbon represented by formula (1) was previously very low. In contrast, the inventors of the present invention have found that when the catalyst contains α-alumina and the average pore size of the catalyst is above 5 nm, the conversion rate is improved. It is believed that this is because the raw material fluorocarbon diffuses into the pores of the catalyst, increasing the contact area between the fluorocarbon and the catalyst. Moreover, α-alumina has excellent durability, so even if the conversion rate decreases during long-term production (at least 50 hours), it can be suppressed.

[0014] On the other hand, Patent Document 1 describes a method for producing fluoroolefins using γ-alumina. However, the crystal structure of γ-alumina changes greatly under high temperature conditions, so when γ-alumina is used as a catalyst, the conversion rate tends to decrease over a long period of production. Non-Patent Document 1 describes a method for producing trifluoroethylene using α-alumina having an average pore diameter of 3.20 nm, and the conversion rate is about 1.2%.

[0015] The method for producing fluoroolefins disclosed in the present invention will be described in detail below.

[0016] (Fluorohydrocarbon represented by formula (1)) In the method for producing a fluoroolefin of the present disclosure, a fluorocarbon represented by the following formula (1) is used as a raw material. CX 1 X 2 F-CX 3 X 4 H……(1) In formula (1), X 1 , X 2 , X 3 and X 4 Each independently represents a hydrogen atom or a fluorine atom, X 1 , X 2 , X 3 and X 4 At least one of them is a fluorine atom.

[0017] Examples of the fluorinated hydrocarbon represented by the formula (1) include the following compounds. CHF 2 CH 3 :1,1-Difluoroethane (HFC-152a) CH 2 FCH 2 F: 1,2-Difluoroethane (HFC-152) CF 3 CH 3 :1,1,1-Trifluoroethane (HFC-143a) CHF 2 CH 2 F: 1,1,2-Trifluoroethane (HFC-143) CF 3 CH 2 F: 1,1,1,2-tetrafluoroethane (HFC-134a) CHF 2 CHF 2 :1,1,2,2-Tetrafluoroethane (HFC-134) CF 3 CHF 2 :1,1,1,2,2-pentafluoroethane (HFC-125)

[0018] Among them, the fluorocarbon represented by formula (1) is preferably at least one selected from HFC-143a, HFC-143, HFC-134a and HFC-134, from the viewpoint of less side reactions and suppressed generation of by-products. Among them, the fluorocarbon represented by formula (1) is preferably HFC-134a, because one type of fluoroolefin can be obtained with high selectivity.

[0019] (Fluoroolefin represented by formula (2)) In the process for producing a fluoroolefin of the present invention, a fluoroolefin represented by the following formula (2) is obtained as a reaction product. CX 1 X 2 =CX 3 X 4 ……(2) In formula (2), X 1 , X 2 , X 3 and X 4 Each independently represents a hydrogen atom or a fluorine atom, X 1 , X 2 , X 3 and X 4 At least one of them is a fluorine atom.

[0020] Examples of the fluoroolefin represented by the formula (2) include the following compounds. CHF=CH 2 :Vinyl fluoride CF 2 =CH 2 :1,1-Difluoroethylene (HFO-1132a) CHF=CHF:1,2-difluoroethylene (HFO-1132(E), HFO-1132(Z)) CHF=CF 2 :Trifluoroethylene (HFO-1123) CF 2 =CF 2 :Tetrafluoroethylene

[0021] Among them, from the viewpoint of usefulness as a refrigerant composition, the fluoroolefin represented by formula (2) is preferably at least one selected from HFO-1132, HFO-1132a and HFO-1123.

[0022] In particular, in the method for producing a fluoroolefin of the present disclosure, from the viewpoint that the reaction proceeds more selectively, the fluorocarbon is preferably HFC-134a, and the fluoroolefin is preferably HFO-1123.

[0023] (catalyst) In the method for producing a fluoroolefin of the present disclosure, a fluorohydrocarbon represented by the formula (1) is brought into contact with a catalyst.

[0024] The catalyst in contact with the fluorinated hydrocarbon contains α-alumina, and the average pore diameter of the catalyst is greater than 5 nm.

[0025] Alumina is a dehydrated product of aluminum hydroxide, and its properties vary depending on the degree of dehydration and crystallinity. Alumina exists in various types, such as γ-alumina, θ-alumina, and α-alumina, depending on its crystal structure. γ-alumina and θ-alumina are called activated alumina, and compared with α-alumina, they have higher free energy of formation and are more thermodynamically unstable. The high-temperature stable phase with high crystallinity is α-alumina, which has a small specific surface area but is thermally stable and has high thermal conductivity. The catalyst used in the method for producing fluoroolefins disclosed in the present invention contains α-alumina. Compared with other alumina structures, α-alumina has a higher conversion barrier from Al-O to Al-F in the presence of hydrogen fluoride. By using a catalyst containing α-alumina, AlF 3 The generation of AlF 3 The generation of ions will lead to catalyst deactivation and decreased selectivity.

[0026] By including α-alumina in the catalyst, the durability of the catalyst is high, and even when the production is carried out for a long time, the decrease in conversion rate is suppressed. In addition, by making the average pore diameter of the catalyst above 5nm, the fluorocarbon diffuses into the pores of the catalyst, the contact area between the fluorocarbon and the catalyst increases, and thus the conversion rate is improved.

[0027] The presence of α-alumina in the catalyst can be confirmed by X-ray diffraction, in other words, by a diffraction pattern obtained by XRD (X-Ray Diffractometer). As XRD, a commercially available device can be used, for example, "SmartLab" manufactured by Rigaku Corporation can be used. If the diffraction pattern contains d=26.62, 35.21, 37.85, 43.43, 52.65 and If the peak of α-alumina is not detected, it can be determined that α-alumina is contained. In addition, this analysis is performed on the catalyst just before contacting with the fluorocarbon or on the catalyst in the same state as that of the catalyst just before contacting with the fluorocarbon.

[0028] The catalyst may also contain compounds other than α-alumina. Examples of compounds other than α-alumina include alumina having a crystal structure different from that of α-alumina, oxides other than alumina, and the like. Examples of alumina having a crystal structure different from that of α-alumina include β-alumina, γ-alumina, θ-alumina, η-alumina, boehmite, and gibbsite. Examples of oxides other than alumina include chromium oxide, copper oxide, iron oxide, nickel oxide, magnesium oxide, zinc oxide, and zirconium oxide.

[0029] Furthermore, the catalyst may contain fluorinated alumina in which α-alumina is fluorinated, aluminum fluoride, or the like as a compound other than α-alumina.

[0030] The catalyst in contact with the fluorocarbon preferably contains α-alumina as the main component, and specifically, preferably contains 65% by mass or more of α-alumina when the mass of the catalyst is 100% by mass. By making the main component of the catalyst α-alumina, the durability of the catalyst is high, and even when the conversion rate is reduced during long-term production, it is also suppressed. The catalyst contains more than 65% by mass of α-alumina, which can be confirmed by performing Rietveld analysis based on the crystal structure of XRD. Specifically, the peak obtained by XRD measurement of the catalyst is compared with the known peak model from each alumina structure and Rietveld analysis is performed to calculate the mass ratio of each crystal structure. The catalyst preferably contains more than 65% by mass of α-alumina, more preferably more than 70% by mass, further preferably more than 75% by mass, particularly preferably more than 80% by mass, and most preferably more than 85% by mass. The catalyst can be 100% by mass of α-alumina, that is, it can be composed only of α-alumina.

[0031] In the crystal structure determination by XRD, the peaks derived from α-alumina are d=26.62, 35.21, 37.85, 43.43, 52.65 and The peak.

[0032] α-Alumina not only functions as a catalyst but also functions as a carrier simultaneously with the catalyst. α-Alumina may also be supported on a carrier other than α-alumina.

[0033] As the support, there can be exemplified carbon, β-alumina, γ-alumina, zirconia, silica and titania.

[0034] The form of the catalyst is not particularly limited, and may be in the form of powder, granules, or spheres.

[0035] α-Alumina is excellent in filling property and flowability of reaction gas when filling a reactor, and therefore, from the viewpoint of handling after about 10 hours of use, a shaped body such as a spherical or granular shape is preferred. The molded body is different from the powder and refers to a molded body obtained by, for example, placing the powder in a mold and performing compression molding.

[0036] A variety of methods for determining the pore structure of a catalyst have been proposed so far. One of the most commonly used methods is to measure the adsorption isotherm by gas adsorption. Nitrogen can be used as a conventional adsorption gas for analyzing pores in the micropore (less than 2 nm) and mesopore (2 to 200 nm) regions. Parameters such as specific surface area, average pore diameter, and pore volume can be obtained from adsorption and desorption isotherms.

[0037] - Specific surface area - It is generally believed that the larger the surface area that can be in contact with the catalyst, the higher the contact frequency between the substrate and the catalyst surface, and the higher the catalyst activity. In order to increase the specific surface area of ​​the catalyst, it is known to reduce the average pore diameter and pore volume. Therefore, among aluminas having multiple crystal structures, there are very few examples of using α-alumina with the smallest specific surface area as a catalyst. However, contrary to previous cognition, it was found that for α-alumina, increasing the average pore diameter that causes a decrease in the specific surface area actually increases the reaction activity in the present disclosure. The specific surface area of ​​the catalyst can be calculated from the monolayer adsorption of nitrogen according to the BET (Brunauer-Emmett-Teller) theory.

[0038] - Average pore diameter - The average pore diameter can be calculated based on the BJH (Barrett-Joyner-Halenda) theory.

[0039] The average pore diameter of the catalyst is measured by the following method. When the average pore diameter of the catalyst is 2 to 200 nm, it is determined by the BET method and the BJH method based on the nitrogen adsorption method. As a measuring apparatus, for example, "3Flex" manufactured by Micromeritics can be used. The average pore diameter was calculated based on the following formula from the specific surface area (S) obtained by the BET method from the adsorption isotherm obtained by the nitrogen adsorption method and the pore volume (V) obtained by the BJH method. D=4V / S D represents the average pore diameter of the sample (m), V represents the pore volume of the sample (m 3 / g), S represents the specific surface area of ​​the sample (m 2 / g). On the other hand, when the average pore diameter of the catalyst is less than 2 nm, it is calculated by the HK (Horvath-Kawazoe) method using the Lennard-Jones function.

[0040] In addition, this measurement is carried out immediately before the catalyst is brought into contact with the fluorinated hydrocarbon.

[0041] The larger the average pore diameter, the more pore spaces with large diameters exist on the surface and inside of the catalyst, so the diffusibility of the fluorohydrocarbon is improved, and the contact frequency between the surface of the catalyst and the fluorohydrocarbon becomes higher, so it is expected to achieve improved reactivity. In addition, if the average pore diameter is too large, the specific surface area of ​​the catalyst will decrease, and there is a tendency to inhibit the role of the catalyst.

[0042] From the above viewpoints, the average pore diameter of the catalyst is 5 nm or more, preferably 5 to 200 nm. The average pore size of the catalyst is preferably 6 nm or more, preferably 10 nm or more, more preferably 12 nm or more, and particularly preferably 15 nm or more. In addition, from the viewpoint of ensuring the specific surface area, the average pore size of the catalyst is more preferably 150 nm or less, further preferably 100 nm or less, particularly preferably 50 nm or less, and most preferably 30 nm or less.

[0043] - Pore volume - The pore volume can be calculated based on the BJH (Barrett-Joyner-Halenda) theory.

[0044] The pores affect the diffusibility of the substrate into the catalyst pores and the strength of the catalyst. The larger the pore volume, the higher the diffusibility of the fluorocarbon into the pores, and the higher the contact frequency between the catalyst and the fluoroolefin, so it is expected to achieve improved reactivity. In addition, if the pore volume is too large, the strength of the catalyst will decrease, and there is a tendency for the strength of the catalyst to decrease.

[0045] From the above viewpoints, the pore volume of the catalyst is preferably 0.002 to 1.20 cm 3 / g. The pore volume of the catalyst is more preferably 0.005 cm 3 / g or more, more preferably 0.01cm 3 / g or more, particularly preferably 0.02cm 3 / g or more. The pore volume of the catalyst is more preferably 1 cm 3 / g or less, more preferably 0.90cm 3 / g or less, particularly preferably 0.80cm 3 / g or less.

[0046] - Bulk density - The bulk density of the catalyst is not particularly limited, but if the bulk density of the catalyst is large, the volume under the same mass becomes small, the reactor can be miniaturized and the efficiency is good. If the bulk density of the catalyst is small, the specific surface area and pore volume of the catalyst increase. From the above viewpoints, the bulk density of the catalyst is preferably 0.4 to 1.5 g / mL. The bulk density of the catalyst is more preferably 0.5 g / mL or more, further preferably 0.6 g / mL or more, particularly preferably 0.7 g / mL or more. In addition, the bulk density of the catalyst is more preferably 1.4 g / mL or less, further preferably 1.3 g / mL, particularly preferably 1.2 g / mL or less.

[0047] (Reaction Conditions) In the method for producing fluoroolefins disclosed in the present invention, the raw gas only needs to contain the fluorocarbon represented by formula (1), and may also contain components other than the fluorocarbon represented by formula (1). The raw gas may be composed only of the fluorocarbon represented by formula (1), or may contain isomers, disproportionated products, impurities, etc. obtained when producing the fluorocarbon represented by formula (1). From the viewpoint of suppressing side reactions and catalyst deactivation, the raw gas preferably contains inert gases such as nitrogen, argon, helium, carbon dioxide, octafluorocyclobutane, etc. in addition to the fluorocarbon represented by formula (1). The inert gas can be used to dilute the target product and by-product hydrogen fluoride. The content of the fluorocarbon represented by formula (1) is preferably 60 mol% or more, more preferably 70 mol% or more, further preferably 75% or more, and particularly preferably 80% or more, relative to the total amount of the raw gas.

[0048] The method for producing a fluoroolefin disclosed herein may be carried out in a gas phase or a liquid phase. Since the fluorocarbon represented by the formula (1) is a gas at room temperature, it is preferred that the fluorocarbon and the catalyst be brought into contact in a gas phase.

[0049] The reactor for contacting the fluorocarbon with the catalyst is not particularly limited in shape and structure as long as it can withstand the temperature and pressure described below. As the reactor, for example, a cylindrical vertical reactor can be cited. As the material of the reactor, glass, stainless steel, iron, nickel, an alloy with iron or nickel as the main component, etc. can be cited. The reactor can be equipped with a heating mechanism such as an electric heater for heating the reactor.

[0050] The catalyst may be contained in any form of a fixed bed type, a fluidized bed type, or a moving bed type. In the case of a fixed bed type, it may be a horizontal fixed bed type or a vertical fixed bed type.

[0051] In addition, the reaction mode can be either flow-through or batch-wise.

[0052] In a fixed bed reactor, various shaped bodies of catalyst-carrying carriers are filled in order to reduce the pressure loss of the reaction fluid. Among them, the method of filling the catalyst in the same way as the fixed bed reactor, using its gravity to move it and discharge it from the bottom of the reactor for regeneration is called a moving bed. In a fluidized bed reactor, in order to use the reaction fluid to make the catalyst layer have fluid-like properties, the catalyst particles are suspended in the reaction fluid and move in the reactor. From the perspective of a wide choice of catalyst shapes and suppressed catalyst wear, a fixed bed reactor is preferred. As a fixed bed reactor, there are tubular reactors and tank reactors. From the perspective of easy control of the reaction temperature, a tubular reactor is preferred. Furthermore, a multi-tube heat exchange reaction in which multiple reaction tubes with small diameters are arranged in parallel and the heat medium is circulated on the outside can be adopted. In addition, when multiple reactors are arranged in series, multiple catalyst layers are provided. The catalyst layer can have at least one section, or there can be more than two sections.

[0053] From the viewpoint of improving the conversion rate, the method for producing fluoroolefins of the present disclosure is preferably carried out in a flow-through manner using a fixed bed reactor (particularly a vertical fixed bed reactor).

[0054] In the method for producing fluoroolefins disclosed herein, the fluorocarbon and the catalyst are preferably brought into contact at a temperature of 300 to 800° C., more preferably at a temperature of 400 to 700° C., and even more preferably at a temperature of 400 to 600° C. If the contact temperature is 300° C. or higher, the conversion rate of the fluoroolefin is improved. If the contact temperature is 800° C. or lower, the decomposition of the fluoroolefin can be suppressed.

[0055] If the contact temperature is 300° C. or higher, the reaction proceeds appropriately, whereas if the contact temperature is 800° C. or lower, the selectivity due to cleavage of the carbon-carbon bond of the raw material decreases, and the disproportionation reaction of the product (unsaturated compound) is suppressed.

[0056] The dehydrofluorination reaction is generally an endothermic reaction, so by properly maintaining the reaction temperature, the conversion rate can be suppressed from decreasing. If the reaction temperature in the catalyst layer rises, the conversion rate of the raw material increases. Therefore, in order to maintain a high conversion rate, it is preferred to maintain the reaction temperature in the catalyst layer at a desired temperature. In order to maintain the reaction temperature in the catalyst layer at a desired temperature, for example, a method of heating the catalyst layer from the outside with a heat medium or the like can be cited. The catalyst usually deteriorates over time as the reaction proceeds. Even when the raw material conversion rate decreases due to catalyst degradation, the catalyst layer can be heated with a heat medium or the like to appropriately maintain or increase the reaction temperature, thereby suppressing the conversion rate from decreasing. When maintaining or increasing the temperature of the catalyst layer, in order to suppress the rapid deterioration of the catalyst, it is preferred to set the temperature rise range below 50°C. The reaction zone begins at the raw gas inlet at the beginning of the reaction. If the catalyst in the raw gas inlet deteriorates over time as the reaction proceeds, the reaction zone will move to the downstream side of the gas flow direction. The generated gas with a lower temperature generated in the reaction zone flows into the vicinity of the downstream side of the reaction zone, so the vicinity of the downstream side usually reaches the lowest temperature in the catalyst layer. In the present disclosure, the temperature of the area of ​​the catalyst layer that reaches the lowest temperature is referred to as the "minimum temperature of the catalyst layer". The temperature further downstream from the vicinity of the downstream side usually increases from the lowest temperature of the catalyst layer as it moves away from the reaction zone.

[0057] In the method for producing fluoroolefins of the present invention, the raw material gas containing fluorocarbons can be supplied to the reactor at room temperature. However, for reasons described later, the raw material gas is preferably appropriately heated (preheated) before being supplied to the reactor. In the case of preheating, the raw material gas is preferably heated to a temperature of 80 to 600° C. before being supplied to the reactor. When preheated to above 80° C., the internal temperature of the reactor is not easy to decrease, and it is easy to achieve the set conversion rate. When preheated to below 600° C., the internal temperature of the reactor is not easy to rise, undesirable reactions are suppressed, and the selectivity is improved.

[0058] The dehydrofluorination reaction in the present disclosure is a molecular increase reaction, so increasing the pressure is unfavorable to the positive reaction. The pressure when the fluorocarbon and the catalyst are brought into contact with each other is not particularly limited, but from the viewpoint of improving the conversion rate, it is preferably -0.05 to 2 MPa, more preferably -0.01 to 1 MPa, and still more preferably normal pressure to 0.5 MPa. In this disclosure, pressure refers to gauge pressure.

[0059] The contact time between the fluorohydrocarbon and the catalyst is preferably 0.5 to 100.0 seconds, more preferably 1.0 to 50.0 seconds, and further preferably 2.0 to 20.0 seconds.

[0060] The above contact time (seconds) is calculated using the following formula. Contact time (seconds) = [length of the reactor filled with catalyst (cm)] / [linear velocity (cm / second)] Linear velocity refers to the speed at which the fluorocarbon passes through the catalyst per unit time.

[0061] In addition, the contact time (g·second / mL) between the fluorocarbon and the catalyst is preferably 1 to 200 g·second / mL, more preferably 5 to 175 g·second / mL, further preferably 7 to 150 g·second / mL, and particularly preferably 10 to 125 g·second / mL. When the contact time (g·second / mL) is above 1 g·second / mL, the conversion rate is improved. When the contact time (g·second / mL) is below 200 g·second / mL, the equipment cost can be suppressed.

[0062] The above contact time (g·sec / mL) was calculated using the following formula. Contact time (g·sec / mL) = [Catalyst filling amount (g)] / [Fluorinated hydrocarbon flow rate (mL / sec)]

[0063] From the viewpoint of further suppressing the decrease in conversion rate, it is preferred to contact the fluorocarbon with the catalyst in the presence of an inert gas. The inert gas is preferably selected from at least one of nitrogen, helium, argon, octafluorocyclobutane and carbon dioxide. Among them, nitrogen is preferred as the inert gas.

[0064] The molar ratio of the fluorinated hydrocarbon to the inert gas in the gas phase is preferably 0.1-30, more preferably 0.5-25.

[0065] From the viewpoint of further suppressing a decrease in conversion rate, it is preferred that the fluorocarbon and the catalyst be brought into contact in the gas phase in the presence of water, wherein the concentration of water is less than 500 ppm based on the total amount of the raw material gas containing the fluorocarbon. The dehydrofluorination reaction in the present disclosure is considered to be carried out by the Lewis acid points on the catalyst surface becoming active points. By carrying out the dehydrofluorination reaction in the gas phase in the presence of water, water is adsorbed on the Lewis acid points on the catalyst surface. It is presumed that by making the concentration of water less than 500 ppm relative to the total amount of the raw material gas containing fluorocarbons, the Lewis acid points on the catalyst surface are destroyed to form a structure similar to the Bronsted acid points, so that the activity reduction of the catalyst is suppressed. As a conventional method for measuring the concentration of water, a method using a commercially available Karl Fischer moisture meter can be exemplified. By making the concentration of water less than 500ppm relative to the total amount of fluorocarbons, the conversion rate is improved, and the target product can be obtained with a high selectivity. From the viewpoint of further improving the conversion rate and being able to obtain the target compound with a higher selectivity, the concentration of water is preferably below 300ppm, more preferably below 100ppm, further preferably below 50ppm, and particularly preferably below 10ppm. The lower the concentration of water, the better, but from the viewpoint that the cost of the dehydration treatment of fluorocarbons and inert gases and the process management will become difficult, it is preferably above 0.5ppm, more preferably above 1ppm.

[0066] The water concentration is the water content in the raw material gas when the fluorocarbon is brought into contact with the catalyst. Alternatively, the water concentration may be replaced by the water content in the raw material gas before it flows into the reactor.

[0067] The method for producing fluoroolefins of the present disclosure preferably further comprises a step of drying the catalyst before contacting the catalyst with the fluorocarbon. By drying the catalyst, water contained in the catalyst is removed, the reactivity to the fluorocarbon is improved, and the conversion rate is increased.

[0068] The method for drying the catalyst is not particularly limited, and the catalyst may be dried before or after the catalyst is filled in the reactor. It is preferred to dry the catalyst after the catalyst is filled in the reactor because the reactor can be preheated while the catalyst is dried. Specifically, it is preferred to dry the catalyst by filling the reactor with the catalyst and heating the reactor while circulating an inert gas.

[0069] In the method for producing fluoroolefins disclosed herein, hydrogen fluoride is generated as a by-product. Hydrogen fluoride has the effect of fluorinating the oxide contained in the catalyst and enhancing the acidic properties. Therefore, it is better to reduce the concentration of hydrogen fluoride. If the concentration of hydrogen fluoride is reduced, the selectivity is maintained, the deactivation of the catalyst is suppressed, and the decrease in reaction activity caused by the decrease in the specific surface area of ​​the catalyst is suppressed. As a method of reducing the concentration of hydrogen fluoride, there is a method of diluting it with an inert gas. The use of an inert gas increases the energy load of the purification step after the reaction, so it is better to appropriately control the use of the inert gas. The concentration of hydrogen fluoride in the reaction is preferably 15 mol% or less. From the viewpoint of extending the life of the catalyst, the concentration of hydrogen fluoride is more preferably 13 mol% or less, further preferably 100 mol% or less, particularly preferably 8 mol% or less, and most preferably 7 mol% or less. In addition, from the viewpoint of productivity and the energy load of the refining process, the concentration of hydrogen fluoride is preferably 0.5 mol% or more, more preferably 0.8 mol% or more, further preferably 1.0 mol% or more, particularly preferably 1.3 mol% or more, and most preferably 1.5 mol% or more.

[0070] The method for producing fluoroolefins disclosed in the present invention is preferably carried out in the presence of an oxidant. The oxidant is preferably oxygen, chlorine, bromine or iodine from the viewpoint of high conversion rate and the ability to obtain the target compound with high selectivity. Among them, oxygen is more preferred. In the present disclosure, the concentration of the oxidant is preferably 0.01 to 21 mol% relative to the raw material gas. From the viewpoint of being able to further increase the conversion rate and being able to obtain the target compound with a higher selectivity, the concentration of the oxidant is more preferably 1 to 20 mol% relative to the raw material compound, further preferably 5 to 18 mol%, and particularly preferably 7.5 to 16 mol%.

[0071] In the present disclosure, the conversion rate refers to the ratio (mol %) of the total molar amount of compounds other than the raw material compound contained in the outflow gas from the reactor outlet to the molar amount of the raw material compound supplied to the reactor. Specifically, the conversion rate refers to the conversion rate at the time when 10 hours have passed after the fluorocarbon and the catalyst have been brought into contact with each other. Generally speaking, from the perspective of productivity, the higher the conversion rate, the better. However, in the dehydrofluorination reaction disclosed in the present invention, it is better to properly control the conversion rate. It is believed that if the conversion rate is controlled, the concentration of hydrogen fluoride refined in the gas phase is reduced, and the catalyst deactivation caused by hydrogen fluoride is suppressed. A method of diluting the gas phase with an inert gas can also be considered, but the use of an inert gas will increase the energy load of the refining process after the reaction, so it is not appropriate to use an excessive amount of inert gas. From the perspective of extending the life of the catalyst, it is preferred to suppress the concentration of hydrogen fluoride in the reaction to less than 15 mol%. Therefore, when the amount of inert gas used is less than the equivalent of fluoroolefins, it is preferred to select an operating condition with a conversion rate of less than 30%. The conversion rate is preferably less than 25%, more preferably less than 20%, further preferably less than 15%, and particularly preferably less than 13%. Too low a conversion rate will reduce productivity and increase the size of the equipment, so it is preferred to select an operating condition with a conversion rate of more than 1.5%. The conversion rate is preferably 2% or more, more preferably 2.5% or more, further preferably 3% or more, particularly preferably 3.5% or more. In particular, in the method for producing fluoroolefins of the present disclosure, by using HFC-134a as the fluorocarbon, the conversion rate does not become too high and the deactivation of the catalyst is suppressed.

[0072] In the present disclosure, the selectivity refers to the ratio (mol %) of the molar amount of the target product contained in the reactor outlet gas to the total molar amount of compounds other than the raw material compound contained in the reactor outlet gas. Specifically, the selectivity is the selectivity at the time when 10 hours have passed after the fluorinated hydrocarbon and the catalyst have been brought into contact with each other. The selectivity is preferably 100% because the post-reaction purification step is unnecessary. However, side reactions may occur in the reaction temperature range required to obtain the desired conversion rate. In order to reduce the amount of waste, reduce the energy load of the post-reaction purification step and extend the life of the catalyst, the higher the selectivity, the better. The selectivity is preferably 90% or more, more preferably 93% or more, and even more preferably 95% or more. In particular, in the method for producing fluoroolefins of the present disclosure, HFO-1123 can be obtained with a high selectivity by using HFC-134a as the fluorocarbon.

[0073] Examples of compounds other than the raw material compounds and the target product contained in the reactor outlet gas include HFC-134, 1,1-difluoroethylene (VdF), E / Z-1,2-difluoroethylene (E / Z-HFO-1132), hydrogen fluoride, carbon monoxide, carbon dioxide, water, and the like.

[0074] According to the method for producing fluoroolefins disclosed herein, the decrease in conversion rate during long-term production (specifically, 50 hours or more) is suppressed. The conversion rate after 10 hours is preferably 70% or more, more preferably 75% or more, and further preferably 80% or more relative to the conversion rate after 50 hours. Example

[0075] The present disclosure will be described in more detail below by way of examples, but the present disclosure is not limited to the following examples within the scope not exceeding the gist of the present disclosure.

[0076] The content of α-alumina contained in the catalysts used in Examples 1 to 13 was measured. (Content of α-alumina in the catalyst) XRD measurement was performed using an X-ray diffractometer "SmartLab" manufactured by Rigaku Corporation, and the diffraction peaks of each crystal phase were subjected to Rietveld analysis to measure the content of α-alumina in the catalyst. The content of α-alumina was evaluated according to the following evaluation criteria. A: The content of α-alumina is 65 mass % or more. B: The content of α-alumina is less than 65 mass %.

[0077] [Example 1] α-alumina (product name "α-alumina, average particle size 0.5 μm", produced by Fujifilm Wako Pure Chemical Industries, Ltd.) was analyzed by X-ray diffraction method, and the result was that the content of α-alumina was evaluated as A. 1 mL of the catalyst was weighed as a catalyst. The catalyst was filled in a reaction tube made of stainless steel (SUS304) with an inner diameter of 1.02 cm and a length of 30 cm and placed in a tubular electric furnace. While nitrogen was flowing, the catalyst filling part was heated to 475°C with a tubular furnace to dehydrate the catalyst. Then, a 0.1 / 1 (mol / mol) mixed gas of nitrogen / HFC-134a was circulated with a contact time of 4.7 seconds to remove HF from HFO-1123. The water concentration of a 0.1 / 1 (mol / mol) mixed gas of nitrogen / HFC-134a was measured using a Karl Fischer water content analyzer and found to be 5 ppm.

[0078] [Example 2~Example 12] In Examples 2 to 12, the HF removal reaction was carried out in the same manner as in Example 1 except that the catalyst was changed and various conditions were changed to the values ​​described in Tables 1 and 2. The catalysts used in Examples 2 to 12 are described below.

[0079] (Example 2) γ-alumina (product name "N612N", produced by JGC Catalysts & Chemicals Co., Ltd.) was pulverized in a mortar to obtain a powder. The obtained powder was calcined at 1300°C for 6 hours in an air atmosphere and analyzed by X-ray diffraction. The evaluation result of the α-alumina content was A. This powder was used as a catalyst.

[0080] (Example 3) γ-alumina (product name "N612N", produced by JGC Catalysts & Chemicals Co., Ltd.) was calcined at 1300°C for 6 hours in air atmosphere. The obtained pellets were analyzed by X-ray diffraction method, and the evaluation result of α-alumina content was A. The pellets were used as catalysts.

[0081] (Example 4) α-Alumina (product name "SA52124", manufactured by Saint-Gobain) was used as a catalyst.

[0082] (Example 5) α-Alumina (product name "SA52238", manufactured by Saint-Gobain) was used as a catalyst.

[0083] (Example 6) α-Alumina (product name "FGL-30", manufactured by Iwatani Chemical Industries, Ltd.) was used as a catalyst.

[0084] (Example 7) α-Alumina (product name "FGL-40", manufactured by Iwatani Chemical Industries, Ltd.) was used as a catalyst.

[0085] (Example 8) α-Alumina (product name "C500", produced by Nippon Light Metal Co., Ltd.) was used as a catalyst.

[0086] (Example 9) α-Alumina (product name "LT303D", produced by Nippon Light Metal Co., Ltd.) was used as a catalyst.

[0087] (Example 10) α-Alumina (product name "AKQ-10", manufactured by Sumitomo Chemical Co., Ltd.) was used as a catalyst.

[0088] (Example 11) γ-alumina (product name "N612N", produced by JGC Catalysts & Chemicals Co., Ltd.) was used as a catalyst.

[0089] (Example 12) As a catalyst, α-alumina (product name "FGH-10", manufactured by Iwatani Chemical Industries, Ltd.) was used.

[0090] [Example 13] In Example 13, the HF removal reaction was carried out in the same manner as in Example 8 except that HFC-134a was replaced by HFC-143.

[0091] The average pore diameter of each catalyst was calculated using "3Flex" manufactured by Micromeritics, based on the following formula using the specific surface area (S) obtained by the BET method from the adsorption isotherm obtained by the nitrogen adsorption method and the pore volume (V) obtained by the BJH method. D=4V / S D represents the average pore diameter of the sample (m), V represents the pore volume of the sample (m 3 / g), S represents the specific surface area of ​​the sample (m 2 / g). In Example 11 where the average pore diameter could not be measured by the above method, it was calculated by the HK method using the Lennard-Jones function.

[0092] The contact time (seconds) was calculated using the following formula. Contact time (seconds) = [length of catalyst filled in the reactor (cm)] / [linear velocity (cm / second)] Linear velocity refers to the speed at which the fluorocarbon passes through the catalyst per unit time.

[0093] The contact time (g·sec / mL) was calculated using the following formula. Contact time (g·sec / mL) = [Catalyst filling amount (g)] / [Fluorinated hydrocarbon flow rate (mL / sec)]

[0094] In the reactions of Examples 1 to 12, the generated gas taken out from the reactor outlet (hereinafter also referred to as "reactor outlet gas") was analyzed by gas chromatography 10 hours after the start of the reaction. Specifically, the analysis was performed using a chromatographic column (product name "DB-1301", manufactured by Agilent, length 60m, inner diameter 0.25mm, film thickness 1μm) installed on a gas chromatograph (product name "GC6850", manufactured by Agilent). The conversion rate of HFC-134a and the selectivity of HFO-1123 were calculated using the molar amount calculated from the area ratio (GCArea%) of the reactor outlet gas.

[0095] (Conversion rate of HFC-134a) It refers to the total molar amount M1 of components other than HFC-134a contained in the reactor outlet gas relative to the molar amount M1 of HFC-134a supplied to the reactor. 134a The ratio (mol%) of Conversion rate of HFC-134a (%) = (M1 / M 134a)×100

[0096] (Selectivity of HFO-1123) Refers to the molar amount of HFO-1123 contained in the reactor outlet gas M 1123 The ratio (mol %) to the total molar amount M1 of compounds other than HFC-134a contained in the reactor outlet gas. HFO-1123 selectivity (%) = (M 1123 / M1)×100

[0097] For Examples 1 and 11, the conversion of HFC-134a was calculated 50 hours after the start of the reaction using the same method as 10 hours after the start of the reaction. In Examples 2 to 10 and 12, since the measurement was not performed 50 hours after the start of the reaction, it is recorded as "-" in Tables 1 and 2. In addition, for Examples 2 to 7, it is presumed that the decrease in the conversion of HFC-134a 50 hours after the start of the reaction was suppressed as in Example 1.

[0098] In the reaction of Example 13, the conversion of HFC-143 and the total selectivity of HFO-1132(E) and HFO-1132(Z) were calculated by the same method as in Example 1 10 hours and 50 hours after the start of the reaction.

[0099] (Conversion rate of HFC-143) It refers to the total molar amount M2 of components other than HFC-143 contained in the reactor outlet gas relative to the molar amount M2 of HFC-143 supplied to the reactor. 143 The ratio (mol%) of Conversion rate of HFC-143 (%) = (M2 / M 143 )×100

[0100] (Total selectivity of HFO-1132(E) and HFO-1132(Z)) It refers to the total molar amount of HFO-1132(E) and HFO-1132(Z) contained in the reactor outlet gas. 1132 The ratio (mol %) to the total molar amount M2 of compounds other than HFC-143 contained in the reactor outlet gas. Total selectivity of HFO-1132(E) and HFO-1132(Z) (%) = (M 1132 / M2)×100

[0101] Table 1 Table 2

[0102] Examples 1 to 10 and 13 are embodiments, and Examples 11 and 12 are comparative examples. As shown in Tables 1 and 2, in Examples 1 to 10 and 13, a process is included for contacting a fluorohydrocarbon represented by formula (1) with a catalyst to produce a fluoroolefin represented by formula (2). The catalyst contains α-alumina and the average pore size of the catalyst is greater than 5 nm. Therefore, the conversion rate is higher than before and the decrease in conversion rate during long-term production is suppressed. On the other hand, in Example 11, the conversion rate decreased significantly when the production was carried out for a long time, compared with Example 1. In Example 12, however, the conversion rate was very low.

[0103] In addition, the disclosures of Japanese Patent Application No. 2022-148004 filed on September 16, 2022 and Japanese Patent Application No. 2022-182072 filed on November 14, 2022 are incorporated herein by reference in their entirety. In addition, all documents, patent applications, and technical standards described in this specification are incorporated herein by reference to the same extent as if the portions incorporated by reference in each document, patent application, and technical standard were specifically and separately described.

Claims

1. A method for producing a fluoroolefin, comprising the step of contacting a fluorocarbon represented by the following formula (1) with a catalyst to produce a fluoroolefin represented by the following formula (2), The catalyst contains α-alumina, The average pore diameter of the catalyst is above 5 nm. CX 1 X 2 F-CX 3 X 4 H……(1) CX 1 X 2 =CX 3 X 4 ……(2) In formula (1) and formula (2), X 1 , X 2 , X 3 and X 4 Each independently represents a hydrogen atom or a fluorine atom, X 1 , X 2 , X 3 and X 4 At least one of them is a fluorine atom.

2. The method for producing a fluoroolefin according to claim 1, wherein: The catalyst contains 65 mass % or more of α-alumina.

3. The method for producing a fluoroolefin according to claim 1 or 2, wherein: The fluorinated hydrocarbon is contacted with the catalyst at a temperature of 300 to 800°C.

4. The method for producing a fluoroolefin according to claim 1 or 2, wherein: The contact time between the fluorinated hydrocarbon and the catalyst is 0.5 to 100.0 seconds.

5. The method for producing a fluoroolefin according to claim 1 or 2, wherein: The contact time between the fluorinated hydrocarbon and the catalyst is 1 to 200 g·sec / mL.

6. The method for producing a fluoroolefin according to claim 1 or 2, wherein: The average pore diameter of the catalyst is 5 to 200 nm.

7. The method for producing a fluoroolefin according to claim 1 or 2, wherein: The pore volume of the catalyst is 0.002 to 1.20 cm 3 / g.

8. The method for producing a fluoroolefin according to claim 1 or 2, wherein: The catalyst is a shaped body.

9. The method for producing a fluoroolefin according to claim 1 or 2, wherein: The fluorinated hydrocarbon is at least one selected from 1,1,1-trifluoroethane, 1,1,2-trifluoroethane, 1,1,2,2-tetrafluoroethane and 1,1,1,2-tetrafluoroethane.

10. The method for producing a fluoroolefin according to claim 1 or 2, wherein the fluoroolefin is at least one selected from the group consisting of 1,2-difluoroethylene, 1,1-difluoroethylene and trifluoroethylene.

11. The method for producing a fluoroolefin according to claim 1 or 2, wherein: The fluorocarbon is 1,1,1,2-tetrafluoroethane, and the fluoroolefin is trifluoroethylene.

12. The method for producing a fluoroolefin according to claim 1 or 2, wherein: contacting the fluorinated hydrocarbon with the catalyst in the presence of an inert gas, The inert gas is at least one selected from nitrogen, helium, argon, octafluorocyclobutane and carbon dioxide.

13. The method for producing a fluoroolefin according to claim 1 or 2, wherein: The method further includes drying the catalyst before contacting the fluorinated hydrocarbon with the catalyst.

14. The method for producing a fluoroolefin according to claim 1 or 2, wherein: contacting the fluorinated hydrocarbon with the catalyst in the presence of water in a gas phase, The concentration of the water is less than 500 ppm based on the total amount of the raw material gas containing the fluorinated hydrocarbon.

15. The method for producing a fluoroolefin according to claim 1 or 2, wherein: The conversion rate after 10 hours from the time when the fluorohydrocarbon is brought into contact with the catalyst is 30% or less.

Citation Information

Patent Citations

  • Manufacturing method of fluoroolefin

    JP2019196347A

  • Gas burner and gas combustion system

    JP2022148004A

  • Robot control system, information processor, information processing method, and program

    JP2022182072A